PENGARUH GAYA KEPEMIMPINAN KONFLIK KERJA STRES KERJA DAN ROTASI KARYAWAN TERHADAP KINERJA BERDASARKAN PERSEPSI KARYAWAN DI RUMAH SAKIT PERTAMINA BALIKPAPAN - Nainggolan, Hermin; Kemala Sari, Gita; Susilo, Erwin (Jurnal GeoEkonomi, 2025)
This study aims to determine the effect of leadership style, work conflict, work stress and employee rotation on performance based on employee perceptions of PT. Pertamina Balikpapan Hospital. The sample used in this study in the Medical Check UP, radiology, laboratory and medical record installations amounted to 54 respondents. The analysis technique used was multiple linear regression analysis, classical assumption test. The statistical analysis test tool used was the SPSS version 24 program. Based on the study, the results obtained that partially, the Leadership Style variable has a positive and significant effect on Employee Performance. This is indicated by the t-count value of 2.868>t-table 2.00958 and a significance value of 0.006 which is less than 0.05. The Work Conflict variable does not have a positive and insignificant effect on Employee Performance. This is indicated by the t-count value of 0.422 <t-table 2.00958 and a significance value of 0.675 which is greater than 0.05. The Work Stress variable has a negative and insignificant effect on Performance. This is indicated by the obtained t-value of -0.615 <ttable 2.00958 and a significance value of 0.541 which is greater than 0.05. The Employee Rotation variable has a positive and significant effect on Employee Performance. This is indicated by the obtained t-value of 3.826> ttable 2.00958 and a significance value of 0.000 which is less than 0.05. That simultaneously the results obtained by Leadership Style, Work Conflict, Work Stress and Employee Rotation have a significant effect on Employee Performance. This is indicated by the obtained F-value of 14.689> F-table 2.56 with a significance value of 0.000 which is less than 0.05.